2018
DOI: 10.1159/000491398
|View full text |Cite
|
Sign up to set email alerts
|

A pan-NADPH Oxidase Inhibitor Ameliorates Kidney Injury in Type 1 Diabetic Rats

Abstract: Background: NADPH oxidases (Nox) is a major enzyme system contributing to oxidative stress, which plays an important role in the pathogenesis of diabetic kidney disease (DKD). We have shown an elevation of renal Nox1, Nox2, and Nox4 in diabetic mice. APX-115, a pan-Nox inhibitor, attenuated the progression of DKD in mice. As the standard diabetic mice cannot fully mimic human DKD, the present study was aimed to show the dose-dependent effect and to provide a confirmatory evidence of APX-115 in attenuating DKD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…131 This orally available compound displays good pharmacokinetics 132 and has been found in mouse studies to have a comparable efficacy to losartan, a drug used in diabetic patients for kidney protection preventing kidney injury and protecting mitochondrial and peroxisomal functions from lipid peroxidation damage. 133 It is also reported to be efficient in the protection of renal injury induced by type 2 diabetes 130 and in streptozotocin-induced type 1 diabetes 133 and has been found to be potentially useful in the treatment of osteoporosis. 131 NOS31 (24, Figure 9 and Table 1), a NOX1-selective inhibitor produced from Streptomyces sp., 134 was found to inhibit tumor growth of several types of cancer cell lines associated with upregulated NOX1 expression, including stomach and colon cancer cell lines.…”
Section: Overview Of the (Patho)physiologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…131 This orally available compound displays good pharmacokinetics 132 and has been found in mouse studies to have a comparable efficacy to losartan, a drug used in diabetic patients for kidney protection preventing kidney injury and protecting mitochondrial and peroxisomal functions from lipid peroxidation damage. 133 It is also reported to be efficient in the protection of renal injury induced by type 2 diabetes 130 and in streptozotocin-induced type 1 diabetes 133 and has been found to be potentially useful in the treatment of osteoporosis. 131 NOS31 (24, Figure 9 and Table 1), a NOX1-selective inhibitor produced from Streptomyces sp., 134 was found to inhibit tumor growth of several types of cancer cell lines associated with upregulated NOX1 expression, including stomach and colon cancer cell lines.…”
Section: Overview Of the (Patho)physiologicalmentioning
confidence: 99%
“…130 APX-115, also known as Ewha-18278, has shown activity against three NOX isoforms (NOX1, NOX2 and NOX4), 130 without acting as a ROS scavenger or as an inhibitor of xanthine and glucose oxidases. 131 This orally available compound displays good pharmacokinetics 132 and has been found in mouse studies to have a comparable efficacy to losartan, a drug used in diabetic patients for kidney protection preventing kidney injury and protecting mitochondrial and peroxisomal functions from lipid peroxidation damage 133 . It is also reported to be efficient in the protection of renal injury induced by type 2 diabetes 130 and in streptozotocin-induced type 1 diabetes 133 and has been found to be potentially useful in the treatment of osteoporosis.…”
Section: Site-specific Ros Inhibitorsmentioning
confidence: 99%
“…NOX5 is also increased in the human diabetic kidney but not encoded by the mouse genome. Nevertheless, it has been shown that forced ectopic expression of NOX5 in mouse models leads to accelerated progression of DKD which could be ameliorated by pan-NOX inhibitors (161,(166)(167)(168).…”
Section: Mitochondrial Bioenergetics and Oxidative Stressmentioning
confidence: 99%
“…APX-115 inhibited renal oxidative stress and prevented albuminuria, glomerular hypertrophy, tubular injury, podocyte injury, fibrosis and inflammation in diabetic kidneys as effectively as losartan alone which is currently used as the standard treatment against kidney injuries in diabetic patients (Kwon et al ., 2017). Moreover, treatment with APX-115 in STZ-induced diabetic rat was also as effective as losartan (Dorotea et al ., 2018). APX-115 is more effective than GKT137831 based on inflammation or fibrosis.…”
Section: Development Of Nox Inhibitor For the Treatment Of Dnmentioning
confidence: 99%